Understanding and Teaching English Word Stress Patterns: Approaches, Challenges, and Practical Solutions for EFL/ESL Instructors and Learners - Islam, Mohammed Nurul (An Overview of Literature, Language and Education Research Vol. 8, 2024)
English word stress patterns are fundamental to intelligibility and fluency in spoken language, making them a crucial component in English as a Foreign Language (EFL) and English as a Second Language (ESL) instruction. However, systematic instruction on word stress placement is often limited, creating challenges for both learners and educators. This chapter investigates various approaches to teaching word stress, common learner difficulties, and practical solutions informed by recent research. Key stress rules are discussed, alongside effective teaching methodologies, including video-based lessons and technology-assisted learning tools that enhance learners’ understanding of stress patterns. Actionable strategies are provided to support EFL/ESL instructors in improving pronunciation skills, boosting intelligibility, and fostering greater fluency in English communication.